Measuring The Resilience of Rural Banks Against Covid-19 Pandemic: Evidence From West Java, Indonesia - Wanda Kharisa Ristyanti; Noer Azam Achsani; Tony Irawan (Business Review and Case Studies, 2023)
The quality of credit and financing provided by rural banks plays a crucial role in determining the continuity of income and interest, ultimately impacting profitability. This study aims to analyse the financial performance dynamics and the factors influencing the profitability of rural banks in West Java, Indonesia during the COVID-19 pandemic by examining the financial reports for the period March 2019 to December 2020 from 26 sampled rural banks. The research employed a multiple linear regression method with REM estimation. Despite the challenging circumstances of the pandemic, the ROA, CAR, and equity values of the rural banks analysed still met the minimum standards set by Bank Indonesia at 1.5%, 8%, and IDR 6 billion, respectively, while the NPL values exceeded the maximum standard of 5%, whereas the NPL values exceeded the maximum standards. The combined factors of CAR, NPL, equity, net income, and the COVID-19 pandemic collectively influence profitability. Specifically, NPL and the COVID-19 pandemic have a significantly negative effect, while net income has a significantly positive effect on profitability. The policy implication that can be implemented to support the resilience of rural banks during crisis are strengthening capital buffer, tightening credit policies, implementing good governance practices, and improving operational cost efficiency. Keywords: rural banks, financial performances, COVID-19 pandemic, profitability